Analisis Korelasi Multidimensi Antara Gangguan Pendengaran Dan Profil Metabolik Terhadap Depresi Pada Lansia - Khuznita Dasa Novita (Publikasi Indonesia, 2025)
depression is a prevalent and often overlooked mental health issue in the elderly, significantly impacting their quality of life. Among its multifaceted risk factors, hearing impairment stands out due to its high prevalence and profound psychosocial consequences. Concurrently, metabolic disorders are also common in this demographic. While the individual links between hearing impairment and depression, and metabolic disorders and general health, are known, their intricate combined effects on depression in older adults remain underexplored. Aims : this study aimed to investigate the differences in demographic characteristics, depression levels, and metabolic profiles between elderly individuals with and without hearing impairment, and to analyze the correlation between specific hearing impairment characteristics, metabolic parameters, and depression. Methods : a cross-sectional study was conducted involving 114 elderly participants (28 without hearing impairment, 86 with hearing impairment). Hearing status was assessed using pure tone audiometry (measuring bone conduction, type, and degree of hearing loss) and the Hearing Handicap Inventory for the Elderly Screening (HHIES). Metabolic parameters included total cholesterol, triglycerides, HDL, LDL, and uric acid. Depression was measured using the Geriatric Depression Scale (GDS). Mann-Whitney U test was used for group comparisons, and Spearman's correlation was employed to assess relationships between variables. Results : elderly individuals with hearing impairment were significantly older (p=0.008) and exhibited significantly higher GDS scores (p=0.049) than those without hearing impairment. Significant differences were also found in total cholesterol (p=0.028), HDL (p=0.003), and LDL (p=0.039). Spearman's correlation revealed significant positive associations between all hearing impairment characteristics (HHIES, bone conduction, type, and degree of hearing loss) and GDS scores (p<0.05). Conversely, metabolic parameters generally showed no significant correlation with GDS. Conclusion : hearing impairment is significantly associated with higher levels of depression in the elderly and is linked to distinct metabolic profiles. These findings underscore the importance of comprehensive screening for both hearing loss and depression in older adults, advocating for integrated geriatric care approaches.